Arc-related black shales as sedimentary archives of sea-level fluctuations and plate tectonics during the late Neoproterozoic: An example from the Bohemian Massif. (January 2021) - Ackerman, Lukáš; Pašava, Jan; Žák, Jiří; Žák, Karel; Kachlík, Václav; Šebek, Ondřej; Trubač, Jakub; Svojtka, Martin; Veselovský, František; Strnad, Ladislav; Santolík, Václav
Abstract: The late Neoproterozoic Lečice black shales and an overlying siliciclastic succession, Bohemian Massif, were deposited in a marine environment on a volcanic arc and provide insights into palaeoenvironmental conditions at the former active margin of northern Gondwana. Field relationships integrated with major/trace element and Mo–Cr–S isotope systematics in two different sections (Štěchovice and Břežany) indicate complex depositional settings intimately connected with the waning activity of the underlying volcanic arc. The Štěchovice black shales represent a deeper part of the basin and were first deposited in weakly anoxic conditions (lower stratigraphic level) with limited terrigenous supply, as reflected by their higher total organic carbon (TOC) and U contents and positive δ 53 Cr, but negative δ 34 Spyrite values accompanied by late-stage silicification by arc-related fluids. An abrupt change to oxygenated conditions and increased terrigenous flux, characterized by lower TOC, U and Mo and coupled, negative δ 53 Cr and δ 98 Mo, is documented in the upper level of the same section. By contrast, the Břežany black shales were deposited in a shallower part of the basin and their composition (e.g., low metal contents, negative δ 53 Cr and δ 98 Mo) suggests oxygenated conditions. Furthermore, the extensive syn-to post-depositional silicification by low-temperature hydrothermal fluids was associated with Si and Ba enrichment and elevated bacterial productivity leading to higher organic matter input. The black shale deposition was terminated by arc uplift, which supplied vast amounts of terrigenous material to the basin and produced a thick flysch sequence deposited at oxygenated conditions. The estimated age of the Lečice black shales ( 580–560 Ma) suggests that their deposition may be linked to interactions between global eustatic sea level changes in response to the late Neoproterozoic glaciations (Gaskiers, Farquar) and dynamic arc topography. Graphical abstract: Image 1 Highlights: Elemental and isotopic (Mo–Cr–S) compositions of the arc-related black shales. Depositional settings and connection to underlying volcanic arc are discussed. Observed variations record significant sea-level fluctuations during the Ediacaran.